Local climate change cultures: climate-relevant discursive practices in three emerging economies - Nick Nash; Lorraine Whitmarsh; Stuart Capstick; Valdiney Gouveia; Rafaella de Carvalho Rodrigues Araújo; Monika dos Santos; Romeo Palakatsela; Yuebai Liu; Marie K. Harder; Xiao Wang (Climatic Change, 2020)
In recent decades, greater acknowledgement has been given to climate change as a cultural phenomenon. This paper takes a cultural lens to the topic of climate change, in which climate-relevant understandings are grounded in wider cultural, political and material contexts. We approach climate-relevant accounts at the level of the everyday, understood as a theoretically problematic and politically contested space This is in contrast to simply being the backdrop to mundane, repetitive actions contributing to environmental degradation and the site of mitigative actions. Taking discourse as a form of practice in which fragments of cultural knowledge are drawn on to construct our environmental problems, we investigate citizens’ accounts of climate-relevant issues in three culturally diverse emerging economies: Brazil, South Africa and China. These settings are important because greenhouse gas (GHG) emissions are predicted to significantly increase in these countries in the future. We conducted semi-structured interviews with a range of citizens in each country using a narrative approach to contextualise climate-relevant issues as part of people’s lifestyle narratives. Participants overwhelmingly framed their accounts in the context of locally-salient issues, and few accounts explicitly referred to the phenomenon of climate change. Instead, elements of climate changes were conflated with other environmental issues and related to a wide range of cultural assumptions that influenced understandings and implied particular ways of responding to environmental problems. We conclude that climate change scholars should address locally relevant understandings and develop dialogues that can wider meanings that construct climate-relevant issues in vernacular ways at the local level.

Experience of extreme weather affects climate change mitigation and adaptation responses - Christina Demski; Stuart Capstick; Nick Pidgeon; Robert Gennaro Sposato; Alexa Spence (Climatic Change, 2017)

Impacts of adaptation and responsibility framings on attitudes towards climate change mitigation - Rachel A. Howell; Stuart Capstick; Lorraine Whitmarsh (Climatic Change, 2016)

Public perception of cold weather events as evidence for and against climate change - Stuart Bryce Capstick; Nicholas Frank Pidgeon (Climatic Change, 2014)